Silicon Treatment on Sorghum Plants Prior to Glyphosate Spraying: Effects on Growth, Nutrition, and Metabolism - Simón, Lesly Analay Yanes [UNESP]; Viciedo, Dilier Olivera; Carbonari, Caio Antonio [UNESP]; Duke, Stephen Oscar; de Carvalho, Leonardo Bianco [UNESP] (MDPI, 2024)
Low doses of glyphosate from application drift can be phytotoxic or stimulate growth of glyphosate-susceptible crops. The application of Si can prevent herbicide-caused plant stress. The effects of Si application (3 mM Si) on low doses (0, 36, 72, and 180 g a.e. ha−1) of glyphosate were determined on Sorghum bicolor in a greenhouse study. Growth parameters, mineral content, metabolite content, and glyphosate and aminomethylphosphonic acid (AMPA) content were measured. Increasing glyphosate content, but no AMPA, was found with increasing glyphosate application rates. Shoot dry weight was increased by 72 g ha−1 of glyphosate when pretreated with Si, and plant height increased in Si-treated plants treated with 72 g ha−1 of glyphosate. Si alone had no effects on growth. Shikimate content was increased by the highest glyphosate rate. Phenylalanine content was generally increased by all glyphosate treatments with or without Si, except for 72 g ha−1 glyphosate without Si. Tyrosine content was increased by 36 and 180 g ha−1 glyphosate without Si. Caffeate content was decreased by Si in the control, and ferulate content was increased with 180 g ha−1 glyphosate in Si-treated plants. Ca levels were reduced by Si at 180 g ha−1 glyphosate. Mn levels were lower than those of the control without Si for all other treatments with Si. The increases in shikimate with the highest glyphosate dose indicated that the herbicide reached its herbicide target and should be causing stress, but the only growth effect was the stimulation of some growth parameters at 72 g ha−1 of glyphosate with Si pretreatment. Similarly, there were increases in some metabolites at some glyphosate concentrations with or without Si. Our results indicate that the rates that we used cause little stress and that Si pretreatment could potentiate glyphosate hormesis for some parameters.
Keywords: herbicide drift; hormesis; N-(phosphonomethyl)glycine; plant nutrition; silicon mitigating effect; Sorghum bicolor